TATBIQ ṬARĪQAT AL-ʿĀB AL-LUGHAWIYYA AL-ʿARABIYYAH LI-TAḤSĪN MAHĀRAT AL-KALĀM WA-AL-KITĀBA LI-L-FAṢL AL-SĀBIʿ BI-MADRASAT AL-THANAWIYYA AL-MUʿALLIMĀT NAHḌAT AL-WAṬAN ANJĀNĪ LUMBUK AL-SHARQIYYA - Nailil Izzati Sa’adatul Asri; Abdul Aziz (El-Tsaqafah : Jurnal Jurusan PBA, 2023)
Language games consist of two words: "games" and "language." Games are activities that develop specific skills or abilities in an enjoyable way. The enjoyment derived from games is not about winning, but rather the pleasant experiences during participation. This research is motivated by the difficulties students face in understanding Arabic lessons and the lack of proficiency among female students in using the Arabic language. The purpose of this study is to determine how the language games method is applied to enhance speaking (maharah kalam) and writing (maharah kitabah) skills in Class VII at MTs. Mu’allimat NW Anjani, as well as to identify the challenges faced when implementing these language games. This study employs a descriptive qualitative approach. Data collection techniques include observations, interviews, and documentation. The results indicate that the application of the language games method is effective, as students show enthusiasm and motivation during lessons. They are attentive and actively engaged, and their desire to learn Arabic is high, although they are not yet fully fluent in using Arabic in daily life. Challenges in applying this method include students' lack of understanding of the games, teachers’ competence in teaching Arabic, and students’ limited interest in Arabic lessons.